Effects of Benthic Protection Extent on Recovery Dynamics of a Conceptual Seafloor Community - Stephenson, Fabrice; Bulmer, Richard H.; Meredyth-Young, Michael; Meysick, Lukas; Hewitt, Judi E.; Lundquist, Carolyn J. (Frontiers in Marine Science, 2019)
Research on disturbance-recovery dynamics has facilitated understanding of species recovery rates, and the likely consequences of human disturbances that operate at large spatial and temporal scales. Benthic Protected Areas (BPA) are a management tool used to protect seafloor communities from disturbance. However, few studies have investigated the benefits of BPAs for benthic communities. A spatially explicit seafloor disturbance model (consisting in 128 x 128 cell grid) was used to simulate recovery dynamics over time in a conceptual benthic community (consisting of eight functional groups (FG)) and investigate interactions between disturbance magnitude and protected area size. The response to disturbance varied between FGs driven by differences in life-history; opportunistic early colonists increased in occupancy whereas other FGs declined, and at high levels of disturbance were extirped. Increasing disturbance accentuated the speed of declines or increases in FG proportional occupancy and increased the recovery times to pre-disturbed levels (if these were not extirped). The inclusion of protected areas lowered the required time for recovery in disturbed areas, with areas adjacent to protected areas recovering faster compared to those further away from the protected areas. Model results suggest that the size of BPAs affects the resilience of the ecosystem, but equally that the effectiveness of protection is heavily dependent on the magnitude of the disturbance in unprotected areas; at high levels of disturbance the permanent loss of the most sensitive FGs occurred in protected areas, resulting in a less functionally diverse and more homogenous conceptual seafloor community. Despite the relatively simple conceptual representation of a benthic community, this heuristic model provides a cost-effective way to explore implications of different management decisions on seafloor communities and highlight model uncertainties for further empirical validation as part of an ecosystem-based management approach.